THE DEVELOPMENT OF STRENGTH QUALITIES IN CADETS USING THE CROSSFIT SYSTEM - Mirzakulov Akrоm Gafurzhanovich (PEDAGOGS, 2024)
Abstract: Sports are widespread all over the world, and various fitness trends are emerging. One of the interesting and popular directions is a new type of strength fitness "crossfit". Crossfit is very different from traditional fitness. It's really a sport. Crossfit is an extreme system of general physical training based on alternating basic movements from various sports (kettlebell lifting, weightlifting, gymnastics, athletics, etc.) The crossfit training system is optimally suited for everyone who cares about their physical fitness. Most people around the world follow the exercises published daily, and this helps them stand out and reach a new level when solving combat tasks, in the ring, in stadiums, in gyms and in everyday life. The good thing about crossfit is that anyone who wants to train can train anywhere and with any set of equipment. Crossfit has convincingly proven its ability to lead to tangible results in functional physical training and to solving a wide variety of tasks.